2019
DOI: 10.1007/s11403-019-00244-7
|View full text |Cite
|
Sign up to set email alerts
|

Growth, unemployment and heterogeneity

Abstract: The paper analyzes unemployment in a medium-run growth model, where aggregate demand and supply interact. On one hand, autonomous demand drives the dynamics of the system, while heterogeneity in the consumption function, due to the presence of unemployment, strengthens the links with supply aspects. On the other hand, both the rate of growth of labor productivity and labor supply are endogenous. Two major results are obtained. First, unemployment allows the reconciliation between aggregate demand and supply. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The third group only includes α , which refers to expectations, which stabilizes the system. Even though the present specification of the expectation function may raise perplexities, Ferri et al ( 2019 ) have shown how the dynamics of the model is robust to changes in the specification of expectations, above all those based upon some form of learning.…”
Section: Sensitivity Analysismentioning
confidence: 89%
See 3 more Smart Citations
“…The third group only includes α , which refers to expectations, which stabilizes the system. Even though the present specification of the expectation function may raise perplexities, Ferri et al ( 2019 ) have shown how the dynamics of the model is robust to changes in the specification of expectations, above all those based upon some form of learning.…”
Section: Sensitivity Analysismentioning
confidence: 89%
“…At the same time, there is uncertainty because the driver cannot work forever. These properties are incorporated in the present model, which is based on the same set up of Fazzari et al ( 2020 ) and by Ferri et al ( 2019 ) except for the consumption function, where its two components (see 3.2 and 3.5 below) are specified in a different way. In fact, the durable consumption function not only maintains the dependence on an exogenous rate of growth ( g *), but it also depends, cyclically and nonlinearly, on the rate of unemployment.…”
Section: Autonomous Demand In a Medium-run Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…As shown by Ferri et al (2001), the regime-switching approach is capable of tempering accelerations in the dynamics with the overall stability of the system and in so doing it can generate endogenous cycles along with Phillips curves of different shapes. The model is a stylized medium-run growth model compatible with structural changes in evolving economies; moreover, it accounts for the role of monetary policy and the interaction between aggregate demand and supply (Fazzari et al 2020;Ferri et al 2019).…”
Section: Introductionmentioning
confidence: 99%